GOOD FEDERATION, CONFEDERATION, BAD FEDERATION: WHY THE AMERICAN CONTROVERSY ON THE FEDERAL UNION SHOULD BE A LESSON FOR THE EUROPEAN UNION - Gabriel C. GHERASIM (Studia Universitatis Babeş-Bolyai. Philologia, 2017)
Good Federation, Confederation, Bad Federation: Why the American Controversy on the Federal Union Should Be a Lesson for the European Union. The aim of this paper is that of revisiting the competing doctrines of federalism in the United States, as they are exemplarily prescriptive about the means and finality of the correspondent process of European integration. Considering the three main glosses on the federal idea in the United States as the Anti-federalist idea, the Confederative experiment and the Federalist focus on strong and centralized government, the present paper will substantively argue for the (in)consistencies of these models and acknowledge the limits of American federal experiences in the uncertain context of the European controversies on the topic.